2022
DOI: 10.1039/d2sc00588c
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonium cations as versatile strongly π-acidic ligands

Abstract: More than a century old, sulfonium cations are still intriguing species in the landscape of organic chemistry. On one hand they have found broad applications in organic synthesis and material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 124 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…2 Surprisingly, their coordination chemistry remained ignored for the last few decades, despite being isolobal and isoelectronic to the tertiary phosphines, which are perhaps the most common ligands in homogeneous catalysis. Indeed, prior to our recent work, 3 the only known sulfonium complexes were reported in the 1980's. These were coordinatively saturated 18e -complexes of the d 6 metals (Mn(I), Mo(0), W(0), and Ru (II)), 4 where the sulfonium ligands could be easily displaced.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…2 Surprisingly, their coordination chemistry remained ignored for the last few decades, despite being isolobal and isoelectronic to the tertiary phosphines, which are perhaps the most common ligands in homogeneous catalysis. Indeed, prior to our recent work, 3 the only known sulfonium complexes were reported in the 1980's. These were coordinatively saturated 18e -complexes of the d 6 metals (Mn(I), Mo(0), W(0), and Ru (II)), 4 where the sulfonium ligands could be easily displaced.…”
Section: Introductionmentioning
confidence: 90%
“…However, we have shown that embedding sulfonium cations within a pincer framework might provide a sufficient protection from complex decomposition. With the aliphatic and aromatic sulfonium pincer ligands, P Et SP and P Ph SP, respectively (Chart 1), we were able to report preparation of the first sulfonium complexes of Rh(I) and Pt(II) 3 two d 8 metal centers widely used in homogeneous catalysis, 5 thus reviving the remarkable chemistry of sulfonium cations as one of the few positively charged ancillary ligands. 6 The presence of a metal-sulfur bond in these complexes was unequivocally confirmed by multinuclear NMR in solution and XRD in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar example are sulfonium ions, which can be regarded as isoelectronic and thus cationic analogues of tertiary phosphines. [24][25][26][27][28] The bonding situation in many cationic ligands is usually represented by several resonance structures that indicate a delocalisation of the positive charge to neighbouring and stabilising atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 107: Sulfonium salts and their applications [219] Unlike phosphines, however, sulfonium salts are not used as spectator ligands, with a few exceptions. [220] Due to their increased reactivity, as a result of the cationic charge, they are rather used as stoichiometric reagents in synthesis (Scheme 107). [219] For example, sulfonium salts can be used as starting materials for S-ylides 335 due to their α-CH-acidity.…”
Section: Sulfonium Salts and Their Synthetic Applicationsmentioning
confidence: 99%